A short and efficient synthesis of valsartan via a Negishi reaction - Ghosh, Samir; Kumar, A. Sanjeev; Mehta, G. N. (Beilstein Journal of Organic Chemistry, 2010)
An efficient synthesis of the angiotensin-II inhibitor valsartan (Diovan®) is presented. Directed ortho-metalation of 5-phenyl-1-trityl-1H-tetrazole (6) and its Negishi coupling with aryl bromide 5 are the key steps of the synthesis. This method overcomes many of the drawbacks associated with previously reported syntheses.
Keywords: antihypertensive therapy; aryl bromide; Negishi coupling; tetrazole; valsartan